Asuransi bagi Akun Game Online untuk Risiko Peretasan - Rahardjo, Clivio; Prasetyo, Abigail (Nagari Law Review, 2024)
Online games are a type of entertainment that is the result of technological developments that occur in this era of globalization. Indonesia is a country with a very large number of active internet users. Most of the active internet users in Indonesia are online game players. Online games are categorized as a digital asset because players can collect various virtual items. Also, the high level and how high the rank that has been achieved in a game account has its own economic value in the eyes of the players. That makes an online game account has its own economic value and is an asset that must be maintained. An online game account owner is also not immune to the risk of losing their account. One of the unavoidable risks is losing an online game account due to hacker attacks. Hackers can hack into a person's online gaming account and take ownership of it. The risk of hacking is a threat that is not expected to happen. By holding online game account insurance from the threat of hacking, it can divert the risk of online game account owners who are exposed to hacker attacks.